Distribution of Pressure in Five General Cosmic Models - Fadel A. Bukhari (Fundamental Research and Application of Physical Science Vol. 3, 2023)
The distributions of radiation pressure and the total pressure of the universe were investigated in the general cosmic models in three time intervals. In the cosmic epoch \(tt\)rm, logarithm of both radiation pressure and the total pressure descend gradually linearly with log(t) . However, in the epoch t = tdec - tv,log(pr(t)) decreases steeply up to t = 6.2104 Myr, then it declines gradually until t = 205.9406 Myr, hence it reduces slowly, whereas log(P (t)) decreases fast up to t = 5.9406Myr, afterwards it descends gradually until t=112.8713 Myr, where it starts declining slowly. Nevertheless, in the time range t= tv-50 Gyr, log(P (t)) reduces fast up to t=1.4458Gyr, then it descends in relatively less rate, while P(t) falls sharply until t=0.7229Gyr, hence it declines rapidly up to tapp= 1.9277Gyr, where P(t) approaches the dark energy pressure \(P_Λ\) As P(t) decreases with cosmic time the horizon expansion speed of the universe dh (t) descends continuously, while the negative values of the horizon expansion acceleration of the universe \(d_h\)(t) increase. On the other hand, the horizon volume speed of the universe expansion \(V_h\)(t) ascends with decreasing P(t), whereas the horizon volume acceleration of the universe expansion \(V_h\)(t) descends. Slightly after t= tapp, \(V_h\)(t) increases to its maximum value at t= tmax, then it starts falling steeply with \(d_h\)(t) towards zero. However, at t= tmax,\(d_h\)(t) surges prominently towards zero, whereas \(V_h\)(t) fluctuates about this value. The drastic changes in \(d_h\)(t), \(d_h\)(t), \(V_h\)(t) and \(V_h\)(t) following the outstanding decrease in P(t) at t= tapp exhibits strong dependence of the cosmic dynamics on the total pressure of the universe.